From simple questions to complex issues, IDNLearn.com has the answers you need. Our community is here to provide detailed and trustworthy answers to any questions you may have.
Sagot :
Let's solve the logical expression [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex] using the given truth values for [tex]\( p \)[/tex] and [tex]\( q \)[/tex].
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & \square \\ \hline T & F & \square \\ \hline F & T & \square \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
For each combination of [tex]\( p \)[/tex] and [tex]\( q \)[/tex], we evaluate the expression step by step.
1. [tex]\( p = T \)[/tex], [tex]\( q = T \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is True, [tex]\( \sim q \)[/tex] is False.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is True and [tex]\( \sim q \)[/tex] is False, so [tex]\( p \wedge \sim q \)[/tex] is False.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is True and [tex]\( p \wedge \sim q \)[/tex] is False. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is True and [tex]\( r \)[/tex] is False, the result is False.
- Therefore, the result is False.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & \square \\ \hline F & T & \square \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
2. [tex]\( p = T \)[/tex], [tex]\( q = F \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is True and [tex]\( \sim q \)[/tex] is True, so [tex]\( p \wedge \sim q \)[/tex] is True.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is False and [tex]\( p \wedge \sim q \)[/tex] is True. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is False, the result is always True regardless of the value of [tex]\( r \)[/tex].
- Therefore, the result is True.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & \square \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
3. [tex]\( p = F \)[/tex], [tex]\( q = T \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is True, [tex]\( \sim q \)[/tex] is False.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is False and [tex]\( \sim q \)[/tex] is False, so [tex]\( p \wedge \sim q \)[/tex] is False.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is True and [tex]\( p \wedge \sim q \)[/tex] is False. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is True and [tex]\( r \)[/tex] is False, the result is False.
- Therefore, the result is False.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & F \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
4. [tex]\( p = F \)[/tex], [tex]\( q = F \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is False and [tex]\( \sim q \)[/tex] is True, so [tex]\( p \wedge \sim q \)[/tex] is False.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is False and [tex]\( p \wedge \sim q \)[/tex] is False. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is False, the result is always True regardless of the value of [tex]\( r \)[/tex].
- Therefore, the result is True.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & F \\ \hline F & F & T \\ \hline \end{array} \][/tex]
So, the complete truth table for [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex] is:
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & F \\ \hline F & F & T \\ \hline \end{array} \][/tex]
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & \square \\ \hline T & F & \square \\ \hline F & T & \square \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
For each combination of [tex]\( p \)[/tex] and [tex]\( q \)[/tex], we evaluate the expression step by step.
1. [tex]\( p = T \)[/tex], [tex]\( q = T \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is True, [tex]\( \sim q \)[/tex] is False.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is True and [tex]\( \sim q \)[/tex] is False, so [tex]\( p \wedge \sim q \)[/tex] is False.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is True and [tex]\( p \wedge \sim q \)[/tex] is False. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is True and [tex]\( r \)[/tex] is False, the result is False.
- Therefore, the result is False.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & \square \\ \hline F & T & \square \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
2. [tex]\( p = T \)[/tex], [tex]\( q = F \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is True and [tex]\( \sim q \)[/tex] is True, so [tex]\( p \wedge \sim q \)[/tex] is True.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is False and [tex]\( p \wedge \sim q \)[/tex] is True. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is False, the result is always True regardless of the value of [tex]\( r \)[/tex].
- Therefore, the result is True.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & \square \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
3. [tex]\( p = F \)[/tex], [tex]\( q = T \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is True, [tex]\( \sim q \)[/tex] is False.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is False and [tex]\( \sim q \)[/tex] is False, so [tex]\( p \wedge \sim q \)[/tex] is False.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is True and [tex]\( p \wedge \sim q \)[/tex] is False. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is True and [tex]\( r \)[/tex] is False, the result is False.
- Therefore, the result is False.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & F \\ \hline F & F & \square \\ \hline \end{array} \][/tex]
4. [tex]\( p = F \)[/tex], [tex]\( q = F \)[/tex]:
- First, we find [tex]\( \sim q \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True.
- Next, evaluate [tex]\( p \wedge \sim q \)[/tex]. [tex]\( p \)[/tex] is False and [tex]\( \sim q \)[/tex] is True, so [tex]\( p \wedge \sim q \)[/tex] is False.
- Now, [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex]. Here, [tex]\( q \)[/tex] is False and [tex]\( p \wedge \sim q \)[/tex] is False. In an implication [tex]\( q \rightarrow r \)[/tex], if [tex]\( q \)[/tex] is False, the result is always True regardless of the value of [tex]\( r \)[/tex].
- Therefore, the result is True.
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & F \\ \hline F & F & T \\ \hline \end{array} \][/tex]
So, the complete truth table for [tex]\( q \rightarrow (p \wedge \sim q) \)[/tex] is:
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & q \rightarrow (p \wedge \sim q) \\ \hline T & T & F \\ \hline T & F & T \\ \hline F & T & F \\ \hline F & F & T \\ \hline \end{array} \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for visiting IDNLearn.com. We’re here to provide clear and concise answers, so visit us again soon.